2018
DOI: 10.1038/s41598-018-36146-0
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6A and 6B inhibit in vitro angiogenesis by induction of Human Leukocyte Antigen G

Abstract: We have previously reported that human herpesvirus 6 (HHV-6) infection of endothelial cells (ECs) induces the loss of angiogenic properties, through the expression of HHV-6 U94, possibly associated to the release of a soluble mediator. It is also known that the soluble isoform of HLA-G exhibits an anti-angiogenic function, important in implantation, transplantation and neoplastic development. In this study, we analyzed the expression of HLA-G in HHV-6 infected ECs, showing that both HHV-6A and HHV-6B infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 33 publications
4
38
0
Order By: Relevance
“…Although a similar prevalence of anti-HHV-6A/B antibodies in the SSc group and healthy controls (76.8 vs. 75%), the prevalence and titer of anti-U94 antibodies were significantly higher in the SSc population (100%, median titer 1:400) compared to controls (46.7%, median titer 1:166) (p < 0.004), confirming previous similar observations in multiple sclerosis patients [45]. Furthermore, consistently with previous observations showing the ability of virus infection to inhibit angiogenesis by a U94-mediated sHLA-G production in endothelial cells [37], we detected increased levels of sHLA-G in HHV-6A/B positive SSc patients compared to negative ones (p < 0.0001). Notably, SSc patients who were both HHV-6A/B and HLA-G positive, also displayed the highest titer of anti-U94 antibodies (p < 0.05), supporting a possible role of HHV-6A/B infection in the disease progression.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Although a similar prevalence of anti-HHV-6A/B antibodies in the SSc group and healthy controls (76.8 vs. 75%), the prevalence and titer of anti-U94 antibodies were significantly higher in the SSc population (100%, median titer 1:400) compared to controls (46.7%, median titer 1:166) (p < 0.004), confirming previous similar observations in multiple sclerosis patients [45]. Furthermore, consistently with previous observations showing the ability of virus infection to inhibit angiogenesis by a U94-mediated sHLA-G production in endothelial cells [37], we detected increased levels of sHLA-G in HHV-6A/B positive SSc patients compared to negative ones (p < 0.0001). Notably, SSc patients who were both HHV-6A/B and HLA-G positive, also displayed the highest titer of anti-U94 antibodies (p < 0.05), supporting a possible role of HHV-6A/B infection in the disease progression.…”
Section: Discussionsupporting
confidence: 91%
“…Aiming to clarify this aspect, HUVEC were infected in vitro with HHV-6A or 6B, and analyzed for the expression of a panel of 84 fibrosis-associated factors. The results showed that HHV-6A and 6B infection induced the upmodulation of several factors, suggesting that infection per se may interfere with the normal functions of endothelial cells [11,37]. Although the TGFβ2 factor, recently recognized as a key factor in fibrosis induction, did not result upregulated by virus infection in HUVECs, other factors belonging to TGFβ superfamily were promoted in particular by HHV-6A, including GREM1 and INHBE, IL-4, IL-5, TNF, and MMP9.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations